Study guides

☆☆

Q: How do you factor x to the sixth minus y to the sixth?

Write your answer...

Submit

Still have questions?

Related questions

(x - y)(x + y)

it is (x-y)(x-y) :)

(x - y)(x + y)

The factoring is as follows: x2 - y2 = (x + y) * (x - y)

It is: (x-y)4

64 x cubed minus y cubed is (4x - y)(16x^2 + 4xy + y^2)

x - y^3 is in its simplest form.

x^2 - y^2 - 4 is in its simplest form.

There are no rational factors.

To factor out the expression: x2y-y3 First factor out one "y": y(x2-y2) The expression x2-y2 is a difference of squares, which factors as well: (y)(x-y)(x+y) This is the simplest factoring of the original expression.

8x - 16y = 8*(x - 2y)

y² - y - 6 = (y + 2)(y - 3)

Let y= ab+(- a)(b) +(-a)(-b) factor out -a y= ab+(-a){b+(-b)} y=ab+(-a)(0) y =ab -------------------(1) now factor out b y= b{a+(-a)}+(-a)(-b) y= b(0) +(-a)(-b) y= (-a)(-b)-----------------(2) equate (1) and (2) (-a)(-b)=ab minus x minus = positive

x2 - y2 = 16 then (x + y)*(x - y) = 16 This has an infinite number of solutions lying on the hyperbola.

X + Y (X + Y) ^2 = (X+Y)(X+Y) Factor = (X + Y)

x - -y = x + y.

2

xcubed-1 Answer::(X-1)(Xsquared+X+1) when you factor xcubed minus a number its the same thing as x cubed minus y cubed and x cubed minus y cubed factors to:: (x-y)(xsquared+xy+y squared) the first factor, (x-y), is the cubed root of the first and the cubed root of the second, so in the answer i have (x-1), which is x cubed minus one cubed :) the second factor, (xsquared+xy+ysquared), you take the first number squared, Xsquared, then the first and second one multiplied together, XY, and then the second number squared, Ysquared, so in the answer i have (xsquared+x+1), which is x squared, then x times 1 which is just x, and positive 1, which is negative 1 squared :) x^3 - 1

Suppose x and y are two POSITIVE numbers so that -x and -y are negative. Then a negative minus a negative = (-x) - (-y) = -x +y If x > y the answer is negative If x = y the answer is zero If x < y the answer is positive

y(y-3)(y+3)

No.

You must use the difference of squares formula: x2 - y2 = (x + y)(x - y) Thus: x2 - 25 = (x + 5)(x - 5).

Your question is like this:X+Y=15, X-Y=5, (X x Y)-X+Y= ?According to my calculations, X=10 and Y=5, therefore (X x Y)-X+Y= 45.

x is y plus 25% of y.

A negative minus a negative turns the latter into a plus positive,for example -6 minus -3 would be :-6 ++ 3 = -3A minus negative always turns into a plus positive...To get more Specific:Suppose x and y are two POSITIVE numbers so that -x and -y are negative. Then a negative minus a negative = (-x) - (-y) = -x +yIf x > y the answer is negativeIf x = y the answer is zeroIf x < y the answer is positive